LO92: Factors contributing to the development of adverse drug events treated in emergency departments. (15th May 2017) - Woo, S.; Cragg, A.; Wickham, M.E.; Ackerley, C.R.; Villanyi, D.; Scheuermeyer, F.X.; Hohl, C.M.
Abstract : Introduction: Adverse drug events (ADEs), unintended and harmful events associated with medications, commonly cause or contribute to emergency department (ED) presentations. Understanding provider, patient and system factors that contribute to their development may assist in developing effective preventative strategies. Ourobjective was to identify factors that contributed to the development of ADEs that caused ED presentations.Methods: We reviewed the charts of ADE patients enrolled in 1 of 3 prospective studies conducted in 3 tertiary care and 1 urban community ED. In the parent studies, researchers enrolled patients by applying a systematic selection algorithm to minimize selection bias, and physicians and pharmacists evaluated patients prospectively to evaluate the causal associations between the drug regimens and patient presentations. Subsequently, a research pharmacist and physician independently reviewed the charts of ADE patients from these cohorts, abstracting data using electronic forms. Reviewers recorded patient, provider and system factors that contributed to the development of ADEs. The main outcome was the presence of at least one contributing factor in the development of an ADE. We used descriptive statistics with appropriate measures of variance. The sample size was determined by enrolment into the primary studies.Results: We reviewed the charts of 670 patients diagnosed with 725 ADEs. We identified ≥1 contributing factors in 62% (95%CI 58-65%) of ADEs. Multiple contributing factors were present in 17% of ADEs (95%CI 13-20%). The most common contributing factors were inadequate patient counseling or instructions about medication use (15%), insufficient laboratory monitoring or follow-up of monitoring tests (12%), lack of staff education (7%), lack of provider adherence with recommended treatment guidelines (7%), and delayed or inadequate clinical reassessment after a medication change (6%). Provider errors in drug administration contributed to 0.3% of ADEs (95%CI 0.0-0.7).Conclusion: Contributing factors were identified for most ADEs. They were often related to inadequate counseling and follow-up, and were rarely the result of errors. Further research is required to understand how communication of medication instructions can be improved. Investments in technologies to reduce provider errors may not significantly reduce the numbers of ADE patients presenting to EDs.